TEM Wave Scattering by a Step Discontinuity on the Outer Wall of a Coaxial Waveguide - Çınar, Gökhan; Nilsson, Börje; Nordebo, Sven; AKŞİMŞEK, HÜSEYİN SİNAN (My University, 2013)
In this paper, the propagation of TEM waves along a coaxial waveguide with a step discontinuity on its outer wall is investigated rigorously by applying the direct Fourier transform and reducing the problem into the solution of a modified Wiener-Hopf equation. The solution for the field terms are determined in terms of an infinite number of unknown coefficients, which satisfy an infinite set of linear algebraic equations. These equations are solved numerically and the effect of area ratio is presented graphically at the end of the analysis. The same problem is also analyzed by applying the mode-matching technique and the results of the two approaches are compared. It is observed numerically that the Wiener-Hopf technique provides a better convergence than the mode-matching technique.
Keywords: Coaxial; discontinuities; electromagnetic (EM) wave propagation and scattering; mode matching; Wiener–Hopf technique